The role of chemical engineering in the organic waste-based circular bioeconomy: what has been done and what still needs to be done. A perspective - Sánchez, Antoni (Frontiers in Chemical Engineering, 2025)
In recent years, various institutions around the world have emphasised the need to change the economic paradigm from linear to circular. In this framework, waste - particularly organic waste - has become a source of opportunities for converting a wide range of organic waste types into bioproducts or bioenergy. This strategy gives rise to the concept of a biorefinery: a multi-product facility combining technologies and processes to maximise the potential of organic waste, going beyond the traditional waste treatment plant. In this context, chemical engineering (CE) is the most suitable discipline for studying the bioeconomy based on organic waste. By its very nature, CE is multidisciplinary and flexible, and is based on mass and heat balances. Thus, it has powerful tools with which to address the technical challenges of organic transformation. Furthermore, Life Cycle assessment (LCA) and Techno-Economical Analysis (TEA) should be based on CE. In turn, LCA and TEA are the main tools that different stakeholders use to successfully implement an organic waste-circular bioeconomy. This perspective paper explores how CE has already helped and could help in the future with the development of a bioeconomy based on organic waste, using both classical and newly developed CE principles and techniques.